2017
DOI: 10.1038/s41598-017-05821-z
|View full text |Cite
|
Sign up to set email alerts
|

RNA structure refinement using NMR solvent accessibility data

Abstract: NMR spectroscopy is a powerful technique to study ribonucleic acids (RNAs) which are key players in a plethora of cellular processes. Although the NMR toolbox for structural studies of RNAs expanded during the last decades, they often remain challenging. Here, we show that solvent paramagnetic relaxation enhancements (sPRE) induced by the soluble, paramagnetic compound Gd(DTPA-BMA) provide a quantitative measure for RNA solvent accessibility and encode distance-to-surface information that correlates well with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
3
29
0
1
Order By: Relevance
“…They found that the inclusion of sPRE data during structural refinement significantly enhanced the quality of the resulting NMR ensemble. (30) Their findings, along with the results of our benchmarking studies, strongly suggest that experimentally-derived SASA contains sufficient restraining power to infer structural ensembles of RNAs. We envision, therefore, that the SASA-based reweighting approach we utilize in this study will emerge as a simple yet robust strategy for using experimentally-derived SASA data to infer atomistic ensembles.…”
Section: Discussionmentioning
confidence: 51%
“…They found that the inclusion of sPRE data during structural refinement significantly enhanced the quality of the resulting NMR ensemble. (30) Their findings, along with the results of our benchmarking studies, strongly suggest that experimentally-derived SASA contains sufficient restraining power to infer structural ensembles of RNAs. We envision, therefore, that the SASA-based reweighting approach we utilize in this study will emerge as a simple yet robust strategy for using experimentally-derived SASA data to infer atomistic ensembles.…”
Section: Discussionmentioning
confidence: 51%
“…Removing the salt increases the strength of the interactions between the nanodiscs and G‐quadruplexes and consequently increases the PRE effect (Figure ). This interesting result suggests that DOTA functionalized nanodiscs could potentially be used to structurally and dynamically probe surfaces of biomolecules similar to previously applied solvent PRE techniques …”
Section: Figurementioning
confidence: 66%
“…The sPRE restraints afford better refined RNA tetraloop structure The 14-mer RNA tetraloop hairpin has often been used as a model system (Borkar et al 2016;Duchardt and Schwalbe 2005;Hartlmuller et al 2017). For its short length and simple secondary structure, even with only the hydrogen-bonding and knowledge-based restraints for the A-form RNA hairpin, the 14-mer RNA structure can already be calculated to a root-mean-square (RMS) deviation of 1.59 Å for all heavy atoms ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the secondary and tertiary structures of an RNA molecule are often intertwined, the incorporation of sPRE restraints is particularly important for RNAs with complex topologies. Note that the previous use of sPRE data for RNA structure refinement (Hartlmuller et al 2017) was demonstrated with two relatively simple RNA structures, and their secondary structures can be readily predicted. In comparison, the secondary structure prediction does not work for the pseudoknot and four-way junction tRNA, the two RNA systems used in Fig.…”
Section: Discussionmentioning
confidence: 99%